1998
DOI: 10.1029/97rs02223
|View full text |Cite
|
Sign up to set email alerts
|

New permittivity measurements of seawater

Abstract: Abstract. We have measured the permittivity of representative samples of natural seawater, synthetic seawater, and aqueous NaC1 solutions over the frequency range 3-20 GHz, in 0.1-GHz steps and over the temperature range -2ø-30øC in 1 ø steps. Additional measurements have been made at spot frequencies (23.8, 36.5, and 89 GHz) and at selected temperatures between -2 ø and 30øC. The data from these measurements have allowed us to deduce an interpolation function for e(v, t, S) in the ranges 2 <-v <-20 GHz, -2 ø … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
140
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(156 citation statements)
references
References 28 publications
(5 reference statements)
7
140
1
3
Order By: Relevance
“…Other studies based on radiometric airborne observations of the ocean-roughened surface (Guillou et al, 1996) have extended and validated existing sea emissivity models at higher frequencies 89 and 157 GHz. Likewise, laboratory experiments with an aqueous NaCl solution and synthetic seawater modeling (Ellison et al, 1998) have demonstrated that the assessment of sea surface emissivity for the interpretation of radar and radiometer data necessarily requires accurate permittivity measurements (better than 5%) of natural seawater in the frequency range 40-100 GHz. In the last fifteen years with the increasing number of satellite platforms hosting increasingly higher spatial resolution new generation microwave sensors, the use of orbital instrument data became more widespread.…”
Section: An Overview On the Emissive Properties Of Surfacesmentioning
confidence: 99%
“…Other studies based on radiometric airborne observations of the ocean-roughened surface (Guillou et al, 1996) have extended and validated existing sea emissivity models at higher frequencies 89 and 157 GHz. Likewise, laboratory experiments with an aqueous NaCl solution and synthetic seawater modeling (Ellison et al, 1998) have demonstrated that the assessment of sea surface emissivity for the interpretation of radar and radiometer data necessarily requires accurate permittivity measurements (better than 5%) of natural seawater in the frequency range 40-100 GHz. In the last fifteen years with the increasing number of satellite platforms hosting increasingly higher spatial resolution new generation microwave sensors, the use of orbital instrument data became more widespread.…”
Section: An Overview On the Emissive Properties Of Surfacesmentioning
confidence: 99%
“…The most frequently used in the past model [44] is becoming increasingly inaccurate with the frequency increase [11,45]. A number of experimental studies of the last two decades [46][47][48][49] resulted in appearance of new updated models. Quite recently, a new permittivity model appeared [10] following the permittivity formulation of [47].…”
Section: Ocean Emission Modelmentioning
confidence: 99%
“…A number of experimental studies of the last two decades [46][47][48][49] resulted in appearance of new updated models. Quite recently, a new permittivity model appeared [10] following the permittivity formulation of [47]. Its coefficients were determined by fitting the new permittivity measurement data, mostly important for L-band BT simulation (for MIRAS on SMOS and Aquarius on SAC-D instruments).…”
Section: Ocean Emission Modelmentioning
confidence: 99%
“…There are several models for the emissivity and permittivity of seawater [33][34][35][36][37][38][39]. FASTEM-6 uses a method that starts from a formulation for the permittivity based on Ellison et al [33].…”
Section: Physical Considerationsmentioning
confidence: 99%
“…FASTEM-6 uses a method that starts from a formulation for the permittivity based on Ellison et al [33]. This describes the complex permittivity with a double Debye model:…”
Section: Physical Considerationsmentioning
confidence: 99%